BASIS FOR ENSURING THE BALANCE OF SPEECH AND LINGUISTIC COMPETENCES IN STATE LANGUAGE LESSONS (On the example of schools where education is conducted in Tajik) (Universal International Scientific Journal, 2026)
This article examines the development of speech and linguistic competencies amongstudents in schools where instruction is conducted in the Tajik language, based on Jim Cummins'theory of bilingualism. Specifically, the principles of BICS (Basic Interpersonal CommunicativeSkills) and CALP (Cognitive Academic Language Proficiency) are utilized to analyze students'communicative abilities partially developed within their socio-natural environments. The studyexplores how these competencies are integrated into current curricula and textbooks, while alsohighlighting the methodological foundations for leveraging students' existing speech experiences tofoster linguistic competence
Keywords: bilingualism; BICS; CALP